2005
DOI: 10.1002/pola.20624
|View full text |Cite
|
Sign up to set email alerts
|

Observation of optical activity in polythiourethane obtained by the controlled cationic ring‐opening polymerization of chiral cyclic thiourethane derived from serine

Abstract: The secondary structure of an optically active polythiourethane [(CH2C*H(CO2Me)NHCOS)n] was evaluated with 1H NMR, IR, and circular dichroism (CD) spectroscopy. Hydrogen bonds between the carbonyl and NH groups in the thiourethane group constrained the main chain of the chiral polythiourethane precisely under the direction of chirality in the main chain, whereas the racemic polymer was also constrained but randomly. The secondary structure of the polythiourethane in CHCl3 changed noticeably in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Furthermore, the inversed carbonyl peaks of the block copolymer were in good agreement with those of poly(S L ) and racemic polymer [poly(S DL )] in DMSO solution. 13 The absorptions resulted from NH and carbonyl groups of the ester and thiourethane moieties in copolymers which were also observed by the IR spectrum, in which the absorptions attributable to the NH moiety of copolymers except poly(S L51 -co-BzS In conclusion, we inversed the chiroptical behavior of optically active polythiourethane segments by sandwiching segments, which would have originated from the conformational inversion confirmed by the NMR spectroscopic study. We think this phenomenon is similar to the manner in which a white piece in the board game 'Othello' flips to black when sandwiched by black pieces.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, the inversed carbonyl peaks of the block copolymer were in good agreement with those of poly(S L ) and racemic polymer [poly(S DL )] in DMSO solution. 13 The absorptions resulted from NH and carbonyl groups of the ester and thiourethane moieties in copolymers which were also observed by the IR spectrum, in which the absorptions attributable to the NH moiety of copolymers except poly(S L51 -co-BzS In conclusion, we inversed the chiroptical behavior of optically active polythiourethane segments by sandwiching segments, which would have originated from the conformational inversion confirmed by the NMR spectroscopic study. We think this phenomenon is similar to the manner in which a white piece in the board game 'Othello' flips to black when sandwiched by black pieces.…”
supporting
confidence: 64%
“…A successful example is the helical inversion of chiral polymers (e.g., polysilane, 1,2 polyacetylene, [3][4][5][6][7][8] and polyisocyanate 9,10 ), whose secondary structures depend on low energy interactions. [12][13][14] As compared with the inescapable steric regulation, the regulation by hydrogen-bonds may be reorganizable due to its lability, i.e., if a chiral polythiourethane comprises both hydrogen-bonding and sterically regulating sequences, the properties of the labile hydrogen-bonding sequence may vary along with the steric regulation. In contrast to synthetic polymers, drastic changes in the high-order structure stabilized by hydrogen-bonds are often observed in mutated proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that polymer was optically active had been confirmed by the specific rotation of −233.3° at a M n of 13.300 g·mol −1 . As an additional advantage, it was observed that hydrogen bonding between the carbonyl and NH groups in the thiourethane group constrained the main chain of the chiral polythiourethane precisely under the direction of chirality; as a consequence the polythiourethane took a secondary structure …”
Section: Chemistrymentioning
confidence: 99%
“…9,10 Recently, polyurethanes and polythiourethanes with main-chain chirality were synthesized by self-polyaddition followed by ring-opening polymerization. 11 The enantiopure polymers formed higher order structures, which were stabilized by much stronger internal hydrogen bonds, compared to the internal hydrogen bonds formed in the unordered racemic polymer.…”
Section: Introductionmentioning
confidence: 99%